Spillover of social norms at work on employees' self-reported private sphere pro-environmental behaviour: A~mixed method investigation - Hans Jaich; Sarah Jastram; Knut Blind (Schmalenbach Journal of Business Research (SBUR), 2023)
This article draws on the Focus Theory of Normative Conduct to examine whether injunctive social norms relating to perceived environmental management practices shape employees' self-reported pro-environmental behaviour in their private sphere. To test our hypotheses, we employed a mixed methods research approach that involved a cross-sectional analysis and a pretest-posttest quasi-experimental field study in the German tourist industry. Our results verify the context-bridging influence of perceived environmental management practices on employees' self-reported private sphere pro-environmental behaviour. Further, they reveal that this relationship is partially mediated by descriptive social norms among co-workers. Thereby, our findings shed light on a thus far neglected dynamic between injunctive and descriptive social norms that constitutes a pathway for contextual spillover. Our study thus challenges the prominent proposition that the influence of injunctive social norms remains restricted to contexts in which the norm is currently salient. The results further develop existing theory by demonstrating how a dynamic interaction between injunctive and descriptive norms can support the emergence and dissemination of social norms across contexts and they reveal how businesses can shape this process.
Keywords: M0; 650; Contextual spillover; Environmental management; Focus Theory of Normative Conduct; Pro-environmental behaviour; Quasi-experimental field study; Social norms